DESAIN DAN UJI COBA LEMBAR KERJA PESERTA DIDIK (LKPD) TERINTEGRASI ISLAM PADA MATERI KIMIA UNSUR - Egi Sastrawan; Elvi Yenti (JEDCHEM (JOURNAL EDUCATION AND CHEMISTRY), 2020)
This research was instigated by the lack of available teaching material that could help students in the learning process, and the unavailability of using Islamic integrated student workbook. This research aimed at knowing the levels of validity and practicality of Islamic integrated student workbook on Chemical Element lesson. It was a Research and Development (R&D) with Borg and Gall model. It was administered at State Senior High School 1 Keritang. The subjects of this research were student workbook media design experts, learning material experts, religious material experts, Chemistry subject teachers, and the students. The object was Islamic integrated student workbook on Chemical Element lesson. The obtained data were the data obtained directly from questionnaire. The instruments of collecting the data were validity and practicality test questionnaires. The obtained data then were analyzed by using qualitative and quantitative descriptive analysis techniques. The developed student workbook was tested, its validity percentage was 84% (very valid) and its practicality percentage was 79.25% (practical). Based on these results, it could be concluded that Islamic integrated student workbook on Chemical Element lesson was valid and practical, so it could be done a limited test.